Preparation of Yeast (Saccharomyces cerevisiae) Biomass from Sugarcane Bagasse - Aderibigbe, F. A.; Adejumo, A. L.; Mohammed, I. A.; Mustapha, S. I.; Akinkahunsi, E. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
In this study, the pretreatment by milling, dilute-acid hydrolysis of sugarcane bagasse, and subsequent fermentation of its glucose product was performed to investigate the effects of process conditions on the production of Saccharomyces cerevisiae. The hydrolysis was carried out using HCl at three substrate concentrations of 20, 25, and 30% (w/v) of bagasse to distilled water. Hydrolysis parameters (time, acid concentration, and temperature) were varied for each case of substrate concentration in full factorial experiments, and an optimum glucose yield of 1.907 g/L was obtained with the 20% (w/v) substrate concentration, at conditions of 10 min time, 0.5 M acid concentration, and 80°C temperature. Thereafter, fermentation experiment was performed with S. cerevisiae in the product of hydrolysis. An optimum ca. 207 yeast number of colonies (yield: 20, 700, 000 cfu/ml) was achieved in 40 h, and the growth of S. cerevisiae was governed by the kinetic equation, ln Xt = 8.4338 + 0.2943t.